ANTISIPASI DAMPAK KENAIKAN MUKA AIR LAUT DAN MITIGASINYA PADA KAWASAN PANTAI GALESONG TAKALAR - Mustika Nur Hasanah; Iphigenia Rara Ranteallo (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Indonesia is an archipelago, and some cities began as coastal towns. Takalar, a coastal city, has experienced social, cultural, and economic development. The Galesong Coastal Area, located in Takalar Regency, South Sulawesi, has various aspects of social, cultural, and financial life, as well as a tourism sector. The relative sea level on the Galesong coast ranges between 6,203 and 6,274 mm per year. On the other hand, sea level rise has tremendous effects on climate change and marine disasters. Some of the effects produced by sea level rise include increased frequency and intensity of flooding, changes in ocean currents, greater mangrove damage, and increased threats to the socioeconomic activities of coastal communities. The purpose of this study is to identify the effects and sources of sea level rise and disasters, hence this study shows the impacts on coastal communities and surrounding marine ecosystems. Based on the declining terrain, socialisation and education of the community on disaster mitigation, and the creation of evacuation routes are some of the impacts that can be anticipated from sea level rise and disasters.